Anethole Attenuates Enterotoxigenic Escherichia coli-Induced Intestinal Barrier Disruption and Intestinal Inflammation via Modification of TLR Signaling and Intestinal Microbiota - Yi, Qingyuan; Liu, Jiaxin; Zhang, Yufeng; Qiao, Hanzhen; Chen, Fang; Zhang, Shihai; Guan, Wutai (Frontiers in Microbiology, 2021)
This study aimed to investigate the effects of dietary anethole supplementation on the growth performance, intestinal barrier function, inflammatory response and intestinal microbiota of piglets challenged with enterotoxigenic Escherichia coli K88. Thirty-six weaned piglets (24 ± 1 d old) were randomly allocated into four treatment groups: (1) sham challenge (CON); (2) Escherichia coli K88 challenge (ETEC); (3) Escherichia coli K88 challenge + antibiotics (ATB); and (4) Escherichia coli K88 challenge + anethole (AN). On day 12, the piglets in the ETEC, ATB, and AN group were challenged with 10 mL E. coli K88 (5×109 CFU/ml), whereas the piglets in the CON group were orally injected with 10 mL nutrient broth. On day 19, all the piglets were euthanized for sample collection. The results show that the feed conversion ratio (FCR) was increased in the Escherichia coli K88-challenged piglets, which could be reversed by the administration of antibiotics or anethole (P < 0.05). The duodenum and jejunum of the piglets challenged with Escherichia coli K88 exhibited greater villous atrophy and intestinal morphology disruption than those of the piglets administered the CON, ATB and AN treatment (P < 0.05). Administration of anethole protected intestinal barrier function and upregulated mucosal layer (mRNA expression of mucin-1 in the jejunum) and tight junction proteins (protein abundance of ZO-1 and Claudin-1 in the ileum) of the piglets challenged with Escherichia coli K88 (P < 0.05). In addition, administration of antibiotics or anethole numerically increased the plasma concentrations of IL-1β and TNF-α (P < 0.1) and decreased the mRNA expression of TLR5, TLR9, MyD88, IL-1β, TNF-α, IL-6 and IL-10 in the jejunum of the piglets after challenge with Escherichia coli K88 (P < 0.05). Dietary anethole supplementation enriched the abundance of beneficial flora in the intestines of the piglets. In summary, anethole could be used as an alternative antibiotic feed additive to protect the intestinal barrier function and alleviate the inflammatory response of piglets.